2020
DOI: 10.1007/s00261-020-02685-2
|View full text |Cite
|
Sign up to set email alerts
|

Is Cambridge scoring in chronic pancreatitis the same using ERCP and MRCP?: A need for revision of standards

Abstract: Grading of chronic pancreatitis (CP) is a clinical and radiologic challenge. Retrograde cholangiopancreatography (ERCP) and magnetic resonance cholangiopancreatography (MRCP) use a version of the Cambridge criteria for ductal evaluation and CP staging, but interchangeability between the modalities lacks validation. This work compares ERCP and MRCP Cambridge scores and evaluates diagnostic performance of MRCP in a large cohort of patients with CP. MethodsA large radiology database was searched for CP patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Furthermore, there is a lack of consistency among the features and diagnostic criteria of different imaging modalities. The diagnostic criteria of MRCP and ERCP are based on the Cambridge scoring system, which focuses on the morphology of the MPD and the appearance of its side branches; however, a lack of strong concordance between the ERCP- and MRCP-based grading systems for CP using the Cambridge criteria has been recently reported[ 8 , 95 , 96 ]. Therefore, the imaging standards for CP may need to be revised to improve the consistency of the diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a lack of consistency among the features and diagnostic criteria of different imaging modalities. The diagnostic criteria of MRCP and ERCP are based on the Cambridge scoring system, which focuses on the morphology of the MPD and the appearance of its side branches; however, a lack of strong concordance between the ERCP- and MRCP-based grading systems for CP using the Cambridge criteria has been recently reported[ 8 , 95 , 96 ]. Therefore, the imaging standards for CP may need to be revised to improve the consistency of the diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
“…117,118 Furthermore, unsatisfactory interobserver agreement is present when using the Cambridge classification, even among abdominal imagers with significant experience. 119,120 Several studies have reported that MRI investigation of changes in the pancreatic parenchyma might more accurately reflect the histopathologic changes related to CP and could be incorporated into a new classification system. 117,[121][122][123][124] Parenchymal signal changes observed by MRI may provide a more comprehensive evaluation of CP [125][126][127] and potentially earlier detection of the pathophysiology, considering that acinar cells comprise greater than 90% of the normal pancreas.…”
Section: Mri Technologymentioning
confidence: 99%
“…However, as the pancreatic ductal system comprises only a small fraction (4%) of the normal pancrea 115,116 and imaging does not directly detect the fibrosis in the parenchyma or loss of acinar cells, the diagnosis of noncalcific CP can be elusive or delayed when using ductal imaging alone 117,118 . Furthermore, unsatisfactory interobserver agreement is present when using the Cambridge classification, even among abdominal imagers with significant experience 119,120 . Several studies have reported that MRI investigation of changes in the pancreatic parenchyma might more accurately reflect the histopathologic changes related to CP and could be incorporated into a new classification system 117,121–124 .…”
Section: Tools For Integrated Pancreatic Analysismentioning
confidence: 99%
“…Currently a stepwise approach is preferred, with endoscopy being a first‐ in‐line treatment because of the vast range of possible treatment options and being less invasive and permanent than surgery 4–6 . Estimates of frequency vary widely but studies show that 27%–76% of CP patients undergo EP, 7–9 with a decline in procedures in the last 20 years due a rise in sensitive imaging modalities replacing ERCP 10,11 …”
Section: Introductionmentioning
confidence: 99%